The Rupaul Paradox: Freedom and Stricture in a Competition Reality TV Show - Hermes, Joke; Kardolus, Michael (Javnost-The Public, 2022)
Drag culture in the 1990s seemed to signify emancipation and liberation of enduring and stifling definitions of gender and sexuality. The uptake of drag and camp in mainstream culture were felt to usher in an era of gender freedom coinciding with new appreciation for popular cultural forms. A quarter century on, popular culture no longer connotes bad taste. The realignment of taste and cultural capital has not coincided with decreased social inequality however, and popular media culture appears to have remained the training ground for what Miller (1993. The Well-Tempered Self. Baltimore: Johns Hopkins University Press) called “the daily organisation of fealty to the cultural-capitalist state.” This paper will inquire into how today’s neo-liberal governmentality and its defining form of offering freedom and stricture at the same time is exemplified by the show hosted by drag queen, singer and television presenter RuPaul (RuPaul’s Drag Race Logo, VH1 2009-today and available on Netflix). Taking as our point of departure our own double-edged sentiments about the show and its host, and the ways queens are divided into role models versus underperformers, we will discuss how race, gender and English proficiency are policed.